Transcriptome Analysis Reveals Drought-Responsive Pathways and Key Genes of Two Oat (Avena sativa) Varieties - Weiwei Xu; Laichun Guo; Chunlong Wang; Liming Wei; Qiang Wang; Qinyong Ren; Xiwu Yang; Chao Zhan; Xiaotian Liang; Junying Wang; Changzhong Ren (Plants, 2024)
To cope with the yield loss caused by drought stress, new oat varieties with greater drought tolerance need to be selected. In this study, two oat varieties with different drought tolerances were selected for analysis of their phenotypes and physiological indices under moderate and severe soil drought stress. The results revealed significant differences in the degree of wilting, leaf relative water content (RWC), and SOD and CAT activity between the two oat genotypes under severe soil drought stress; moreover, the drought-tolerant variety exhibited a significant increase in the number of stomata and wax crystals on the surface of both the leaf and guard cells; additionally, the morphology of the guard cells was normal, and there was no significant disruption of the grana lamella membrane or the nuclear envelope. Furthermore, transcriptome analysis revealed that the expression of genes related to the biosynthesis of waxes and cell-wall components, as well as those of the WRKY family, significantly increased in the drought-tolerant variety. These findings suggest that several genes involved in the antioxidant pathway could improve drought tolerance in plants by regulating the increase/decrease in wax and cell-wall constituents and maintaining normal cellular water potential, as well as improving the ability of the antioxidant system to scavenge peroxides in oats.